THEORETICAL AND APPLIED PRINCIPLES OF COVERT INVESTIGATIVE (DETECTIVE) ACTIONS: GENESIS AND DEVELOPMENT PROSPECTS - Lykhova, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Review of the monograph of the candidate of legal sciences, professor of the Department of Criminal Law and Procedure of the National Aviation University Babikov Oleksandr Petrovych "Theoretical and applied principles of covert investigative (search) actions: genesis and development prospects." The author notes that the peer-reviewed work provides a grounded and consistent rationale and statement of positions regarding the institution of covert investigative (search) actions. The reviewer concludes that the monograph is a complete educational product prepared at a high scientific and educational-methodical level and will be useful for law enforcement officers, scientific and pedagogical workers and students of higher education.